NEW CONCEPTIONS OF INTERNATIONAL CRIMES AGAINST HUMANITY AND POSSIBLE JURISDICTION OF THE INTERNATIONAL CRIMINAL COURT ON ENVIRONMENTAL CRIMES - e Silva, Natan Alves de Morais; Cordeiro, Pedro Augusto da Silva; Stival, Mariane Morato (CIPEEX, 2022)
THE ARTICLE AIMS TO DEVELOP AN ANALYSIS ON THE INTERNATIONAL CRIMINAL COURT JURISDICTION TO ACT ON ENVIRONMENTAL CRIMES AND CRIMES AGAINST HUMANITY. CONSIDERING THE OBSERVANCE AND PREVALENCE OF FUNDAMENTAL RIGHTS, AS WELL AS THE PRINCIPLE OF SOVEREIGNTY, CONSTITUTIONAL FOUNDATION OF THE BRAZILIAN STATE. THE DISCUSSION ON THE SUBJECT AIMS TO ANALYZE, DEFINE AND CHARACTERIZE ENVIRONMENTAL RESPONSIBILITY, AS WELL AS ESTABLISH MEASURES THAT EXPAND INTERNATIONAL JURISDICTION TO ACT IN ENVIRONMENTAL CRIMES. REGARDING METHODOLOGY, THE INITIAL PROPOSAL CONSISTS OF USING THE BIBLIOGRAPHICAL RESEARCH TECHNIQUE IN RELATION TO THE THEME (BOOKS, ARTICLES, THESES AND DISSERTATIONS), AND PERTINENT NATIONAL AND INTERNATIONAL LEGISLATION, WITH THE PURPOSE OF IDENTIFYING THE DIFFERENT INTERPRETATIONS OF THE AUTHORS ON THE SUBJECT. THE RESEARCH APPROACH IS HYPOTHETICAL-DEDUCTIVE. WE SEEK TO VERIFY THE POSSIBLE ACTION OF THE INTERNATIONAL CRIMINAL COURT IN CASES OF ENVIRONMENTAL TRAGEDIES, CONSIDERED AS ECOCIDE IN BRAZIL, AND TO PRESENT CONTRIBUTIONS TO SOLVE THE PROBLEM. WITH THE PURPOSE OF RAISING SPECIFIC DATA ON MAJOR TRAGEDIES, UNDERSTANDING THE PROBLEMS CAUSED TO THE POPULATIONS AND TO THE ENVIRONMENT, AND FINALLY, VERIFYING THE POSSIBLE CONTRIBUTIONS OF INTERNATIONAL ENVIRONMENTAL LAW IN CASES OF ECOCIDE IN BRAZIL.